The Pesantren Education System (A Case Study of the Curriculum and Learning Process of Pesantren Sulaimanyah Medan Syarif) - Harahap, Azwar Amid; Nasution, Hasan Bakti; Nurmawati, Nurmawati (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to describe the curriculum content, analyze the learning process, and identify the challenges and supporting factors in implementing the curriculum at Pesantren Sulaimaniyah Medan Syarief. The research was conducted using a qualitative field research approach. The research instruments included observation, interviews, and document analysis. The primary and secondary data sources for this research are obtained from Pesantren Sulaimaniyah Medan Syarief. The results showed that the analysis of curriculum materials at Pesantren Sulaimaniyah Medan Syarief is using the school curriculum (independent), the education system at Pesantren Sulaimaniyah Medan Syarief is muadalah by carrying out cooperation with the Ministry of Religion, the subjects at Pesantren Sulaimaniyah Medan Syarief are general subjects and pesantren subjects, the study group division system is divided into pre tahfidz, tahfidz, tardris, ibtida'i, ihdzari, tahta takamul, takamul, and there are daily, weekly and monthly programs. The learning process at Pesantren Sulaimaniyah Medan Syarief is the selection to enter the pesantren, class division system, learning methods, media, learning evaluation, and assessment system. Supporting factors at Pesantren Sulaimaniyah Medan Syarief are the learning environment, learning targets that must be achieved, good human resources (HR), parental and community support, and complete facilities and infrastructure.